Development of Digital Library Based on Senayan Library Management System (Slims) 9 Bulian at SMA Yapida Gunungputri Bogor - Saefudin; Widyasari; Zainal Abidin Arief (TOPAZART, 2023)
The purpose of this research is to develop a Digital Library based on Senayan Library Management System (Slims) 9 Bulian at SMA YAPIDA Gunungputri Bogor and test its feasibility and effectiveness. The research method used is Research and Development (R&D) with the development model used is the ADDIE model, which is integrated with the Waterfall model at the development stage. The research steps are analysis, design, development or coding, product trials, and evaluation. The subjects in this study were students of grade XII science. This study used the validation of 3 experts, namely design, media and material experts and conducted an effectiveness test using the N-Gain test. The findings in this study show that the development of digital libraries based on the Senayan Library Management System (SliMS) 9 Bulian is feasible and effective to use.